FISCAL POLICY AS THE PRIMARY TOOL TO AFFECT THE STRENGTH OF THE CAPITAL MARKETS - Boburjon Turanboyev Qodirjon o‘g‘li; Musabekov Sherali Nazarali o‘g‘li (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Fiscal policy is a powerful tool used by governments to achieve macroeconomic objectives, including the strength of capital markets. Capital markets are critical to economic growth and job creation, and fiscal policy can influence them through changes in government spending and tax rates. However, there are limitations and challenges to using fiscal policy, such as slow implementation and political pressures. Governments must carefully consider the impact of their fiscal policies on the economy and use other policy tools when necessary. Despite these limitations, fiscal policy remains a crucial tool for promoting economic growth and prosperity. This article explores how fiscal policy can impact capital markets, the challenges and limitations associated with its use, and the importance of careful consideration when implementing fiscal policies. Ultimately, governments must balance their desire to influence capital markets with the need to maintain a stable and thriving economy.